Falls and Depression in Men: A Population-Based Study. Issue 1 (January 2018) - Stuart, Amanda L.; Pasco, Julie A.; Jacka, Felice N.; Berk, Michael; Williams, Lana J.
The link between falls and depression has been researched in the elderly; however, little information is available on this association in younger adults, particularly men. This study sought to investigate the link between major depressive disorder (MDD) and falls in a population-based sample of 952 men (24-97 years). MDD was diagnosed utilizing the Structured Clinical Interview for DSM-IV-TR Research Version, Non-Patient edition, and categorized as 12-month/past/never. Body mass index and gait were measured; falls, smoking status, psychotropic medication use, and alcohol intake were self-reported as part of the Geelong Osteoporosis Study 5-year follow-up assessment. Thirty-four (3.6%) men met criteria for 12-month MDD, and 110 (11.6%) for past MDD. Of the 952 men, 175 (18.4%) reported falling at least once during the past 12 months. Fallers were older (66 [interquartile range: 48-79] vs. 59 [45-72] years, p = .001) and more likely to have uneven gait ( n = 16, 10% vs. n = 31, 4%, p = .003) than nonfallers. Participants with 12-month MDD had more than twice the odds of falling (age-adjusted odds ratio: 2.22, 95% confidence interval [1.03, 4.80]). The odds of falling were not associated with past depression ( p = .4). Further adjustments for psychotropic drug use, gait, body mass index, smoking status, blood pressure, and alcohol did not explain these associations. Given the 2.2-fold greater likelihood of falling associated with depression was not explained by age or psychotropic drug use, further research is warranted.